2016
DOI: 10.21278/brod67202
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Objective Approach for Determining the Number of Blades on a Naca Marine Propeller

Abstract: SummaryThis paper numerically discusses how the performance of a NACA marine propeller is affected by the number of blades, which is one of the most crucial geometrical parameters determining the performance of a propeller. Results are presented in terms of the hydrodynamic and structural parameters. The results show that changing the number of blades changes the hydrodynamic efficiency, torque, thrust, cavitation behaviour and structural stiffness of the propeller nonlinearly. Furthermore, it is shown that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
(7 reference statements)
1
1
0
Order By: Relevance
“…Similar to what was found by [24], the increase of thrust coefficient at Z=5 was basically occurred due to the dark blue contour region (low pressure area), as clearly displayed in Figure 7 (c). It can be concluded here that the increase of blade numbers will reduce the static pressure around the propeller blade as supported by [25]. Referring to the CFD simulation results above, it can be concluded that the propeller performance achieved maximum đťś‚ within the range of 0.8 ≤ J ≤ 0.9 regardless of a number of blades (see Table 3).…”
Section: Resultssupporting
confidence: 51%
“…Similar to what was found by [24], the increase of thrust coefficient at Z=5 was basically occurred due to the dark blue contour region (low pressure area), as clearly displayed in Figure 7 (c). It can be concluded here that the increase of blade numbers will reduce the static pressure around the propeller blade as supported by [25]. Referring to the CFD simulation results above, it can be concluded that the propeller performance achieved maximum đťś‚ within the range of 0.8 ≤ J ≤ 0.9 regardless of a number of blades (see Table 3).…”
Section: Resultssupporting
confidence: 51%
“…The more the number of blades, the greater the aerodynamic interference between the blades. In this paper, the commonly used double blade propeller is selected (Mohammad and Saber, 2016; Bakhtiari and Ghassemi, 2020).…”
Section: Propeller Designmentioning
confidence: 99%